An aptamer-enabled DNA nanobox for protein sensing - Tang, Marco S.L.; Shiu, Simon Chi-Chin; Godonoga, Maia; Cheung, Yee-Wai; Liang, Shaolin; Dirkzwager, Roderick M.; Kinghorn, Andrew B.; Fraser, Lewis A.; Heddle, Jonathan G.; Tanner, Julian A. (Nanomedicine, 2018)
DNA nanostructures can show dynamic responses to molecular triggers for a wide variety of applications. While DNA sequence signal triggers are now well-established, there is a critical need for a broader diversity of molecular triggers to drive dynamic responses in DNA nanostructures. DNA aptamers are ideal; they can both seamlessly integrate into DNA nanostructure scaffolds and transduce molecular recognition into functional responses. Here, we report construction and optimization of a DNA origami nanobox locked by a pair of DNA double strands where one strand is a DNA aptamer targeting the malaria biomarker protein Plasmodium falciparum lactate dehydrogenase. The protein acts as the key which enables box opening. We observe highly specific protein-mediated box opening by both transmission electron microscopy and fluorescence. Aptamer-enabled DNA boxes have significant potential for enabling direct responses to proteins and other biomolecules in nanoscale diagnostics, drug delivery and sensing devices. A DNA origami box can sense the malaria diagnostic protein Plasmodium falciparum lactate dehydrogenase (PfLDH), using a targeted aptamer that leads to box opening and a change in fluorescence signal upon protein binding. [Display omitted]